Diagnosis and Treatment of Pediatric Feeding Disorders: A Narrative Literature Review - Hugo Pergeline; Léo Gonnet; Arnaud Fernandez; Federico Solla; François Poinso; Jokthan Guivarch (Children)
Background/Objectives: The definitions of feeding disorders of infants and young children were historically based on a dichotomic organic/non-organic vision. Since 2019, a new definition of pediatric feeding disorders (PFDs) has reshaped the understanding of these disorders with a global vision. The aim of this study is to obtain a better understanding of the diagnostic criteria for general practice, both by exploring the evolution of classifications and by clearing the actual definition of PFDs and their possible treatments. Methods: We conducted a narrative review of the literature, including 36 articles about PFDs, excluding adolescents, anorexia nervosa, bulimia, pica, rumination, and specific neurodevelopmental or chronic pediatric disorders. We summarized these studies in three parts: the specific classifications for children before puberty, the current definition, and the clinical guidelines. Results: Concerning the history of the classifications, we summarized the studies of Chatoor and Kerzner and the older pediatric vision of failure to thrive. For the definition of pediatric feeding disorders, we presented this new category involving at least one out of four domains: medical, nutritional, feeding skills, or psychosocial. For the main clinical guidelines, we presented recommendations for both severe and common PFDs in each altered domain for use in daily practice. Conclusions: The new definition promotes a transdisciplinary vision of childhood feeding disorders, which considers each of the intricate domains of PFDs. Using common terminology for PFDs could help all healthcare providers, families, and researchers to better understand and address PFDs.